2009
DOI: 10.1002/ceat.200800566
|View full text |Cite
|
Sign up to set email alerts
|

Near Zero CO2 Emissions in Coal Firing with Oxy‐Fuel Circulating Fluidized Bed Boiler

Abstract: Carbon capture and storage is a concept to reduce greenhouse gas emissions of energy production from fossil fuels. In oxy-fuel combustion, the fuel is burned in a mixture of oxygen and recycled flue gas. This generates CO 2 -rich flue gas from which the CO 2 is easily separated and compressed. Foster Wheeler Power Group is developing the existing design tools and process models of air-fired circulating fluidized bed boilers to implement specific features of oxycombustion. The validation data is produced from b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(17 citation statements)
references
References 7 publications
1
16
0
Order By: Relevance
“…In air atmosphere, CaO and CaSO 4 are the main forms of calcium, which indicates that CaCO 3 decomposes into CaO first and then part of CaO reacts with SO 2 to form CaSO 4 . The calcium conversion to CaSO 4 is about 30%, which is close to the results in the references [15,16]. In O 2 /CO 2 atmosphere, CaO, CaCO 3 and CaSO 4 are all main forms in the ash.…”
Section: Desulfurization Efficiency Of Limestone Under Different Atmosupporting
confidence: 80%
See 2 more Smart Citations
“…In air atmosphere, CaO and CaSO 4 are the main forms of calcium, which indicates that CaCO 3 decomposes into CaO first and then part of CaO reacts with SO 2 to form CaSO 4 . The calcium conversion to CaSO 4 is about 30%, which is close to the results in the references [15,16]. In O 2 /CO 2 atmosphere, CaO, CaCO 3 and CaSO 4 are all main forms in the ash.…”
Section: Desulfurization Efficiency Of Limestone Under Different Atmosupporting
confidence: 80%
“…Lawrence [14] found even without lime injection the SO 2 emissions were dramatically decreased with oxy-CFB combustion. VTT's pilot experiment showed that the desulfurization efficiency of limestone during oxy-CFB combustion can reach 98% [15], much higher than that in air combustion. Jia et al [16] observed that the sulfur capture was lower in oxy-CFB combustor at 850 o C than air-fired, ranging from 65% to 78.2%.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…One is a 20 MW th PC boiler and the other is a circulating fluidised bed (CFB) combustor of 15 MW th operating in air-mode and 30 MW th operating in oxy-mode. It is believed that an oxy-fuel CFB combustor will be an important candidate for new coal fired power plants [6][7][8] mainly because the circulation of solids in the combustor can help to an effective control of the temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Any future improvements in their energy consumption will also improve the efficiencies claimed in this work. In particular, it should be highlighted that the Ca looping system described in this article will benefit the fast development that is expected for oxy-CFB technology, 26 which is an enabling technology for the Ca looping process described in this work.…”
Section: Simulation Resultsmentioning
confidence: 98%